Analisis Kendala dan Strategi Implementasi Augmented Reality Berbasis BIM untuk Quality Control Pekerjaan MEP pada Proyek Rumah Sakit X - Fadhil Muhammad Suheri; Ari Syaiful Rahman Arifin; Faisal Ashar; Muvi Yandra (Lembaga Yasin AlSys, 2026)
The application of digital technology in construction is developing through the integration of Building Information Modeling (BIM) and Augmented Reality (AR), particularly to improve the effectiveness of quality control during the project implementation stage. However, the implementation of AR in construction work still faces obstacles, particularly related to workflow integration, human resource readiness, and the absence of Standard Operating Procedures (SOP). This study aimed to analyze the obstacles and formulate strategies for implementing BIM-based AR in the quality control of Mechanical, Electrical, and Plumbing (MEP) work on Hospital X project. This study used a descriptive qualitative approach with an evaluative design. Data were collected through observation, interviews with nine informants, and documentation, and were then analyzed using coding and categorization techniques. The results showed that BIM-based AR was able to improve visualization and the accuracy of MEP installation verification through comparison between digital model overlays and actual field conditions. However, its use had not been optimal because it had not been systematically integrated into the quality control workflow. The main obstacles identified were managerial in nature, especially the absence of SOP as an implementation reference. Thus, the required strategies include integrating AR into the quality control workflow, preparing operational guidelines, and developing standardized documentation to support the improvement of MEP work quality in construction projects.